2x-3=5+3x

Simple and best practice solution for 2x-3=5+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-3=5+3x equation:


Simplifying
2x + -3 = 5 + 3x

Reorder the terms:
-3 + 2x = 5 + 3x

Solving
-3 + 2x = 5 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-3 + 2x + -3x = 5 + 3x + -3x

Combine like terms: 2x + -3x = -1x
-3 + -1x = 5 + 3x + -3x

Combine like terms: 3x + -3x = 0
-3 + -1x = 5 + 0
-3 + -1x = 5

Add '3' to each side of the equation.
-3 + 3 + -1x = 5 + 3

Combine like terms: -3 + 3 = 0
0 + -1x = 5 + 3
-1x = 5 + 3

Combine like terms: 5 + 3 = 8
-1x = 8

Divide each side by '-1'.
x = -8

Simplifying
x = -8

See similar equations:

| (5/6)=((w-2)/4) | | m-10n=6 | | 5(x-2)=16 | | 1=x+0.56x | | 37=5w-13 | | p(x)=2x^2+5x+1 | | 3x^2+26x=16 | | 5x+43=8x-19 | | 12z+28-7z-3= | | 6x+1=34-5x | | 32+(x-2)+32+(x-2)= | | 1.95y+6.834=7.65y-19.8591 | | 70=-7 | | 3*(x-31)=x-13 | | 5-4(6-3)= | | 13x-32=9x-4 | | 182=7(-5v-9) | | 7+8(3-9)= | | 13x+15=11x-2 | | (-3i)(8i)= | | 6-6x(9-9)/1/(2x6) | | 31/7=93/t | | -8•(7/2) | | -8•(-7/2) | | 9x-25=94 | | 14/9=42/t | | g(v)=3v+4 | | 28X=7X-14 | | 36=16t^2+48t | | 1/4x20/4 | | 12/16=42/x | | 28v^5x^2y^3-16v^9x^7= |

Equations solver categories